Illegitimate Tasks, Stress and Mental Health: A Study of the Correlates and Consequences of Toxic Workplaces (Journal of Asian Development Studies, 2025)
Employee well-being is greatly impacted by workplace dynamics, and one major stressor that contributes to psychological anguish is unlawful tasks. Illegitimate tasks—those deemed needless or irrational—violate workers' sense of justice and professional identity, which increases stress levels at work. This study investigates the relationship between stress, anxiety, depression, illegitimate tasks, and the more general idea of a toxic workplace. Since illegal tasks erode job satisfaction and foster sentiments of unfairness and resentment, they are closely linked to occupational stress. Illegitimate activities are also frequently a sign of a hostile workplace culture that includes bullying, a lack of transparency, bad leadership, and irrational demands. Because toxic workplaces promote unhealthy power dynamics, interpersonal disputes, and a lack of organizational support, they worsen the negative impacts of stressors. Workers in these settings may suffer from burnout, cognitive decline, and a higher risk of turnover and absenteeism. In addition to worsening mental health in individuals, the combined psychological toll of these issues lowers morale and productivity at work. Proactive organizational tactics, such as transparent task delegation, equitable workload sharing, and encouraging leadership, are needed to address these problems. Illegitimate tasks and toxic job conditions can be lessened with interventions including encouraging open communication, providing mental health supports, and cultivating a pleasant work culture. Future studies should look more closely at the psychological effects over the long run and consider practical ways to improve worker satisfaction and organizational viability.